Siri' Culture-Based Psychoeducation Services in an Effortalleviation of Adolescent Problems Due to the Negative Impact of Globalization - M Yunus Sudirman; Muhammad Junaedi Mahyuddin; Fitrianti Sulaiman; Elihami Elihami; Imam Mursyid (Universitas Muhammadiyah Enrekang, 2023)
Education is an entity that is very close to human culture and civilization. In the era of disruption, progress in science and technology has been seen and can be enjoyed by mankind. Culture as a national character, clearly cannot fade and its existence must be strengthened.Indonesia has a wealth of culture including local wisdom values ​​contained in each region, these values ​​contain positive meanings to be maintained and implemented today. This research is based on the idea that socio-cultural changes that are so fast make teenagers. So one of the efforts to maintain the values ​​of local wisdom that exist in Indonesia, needs to be revitalized again, one of which is through siri' culture-based psychoeducation services in an effort to alleviate youth problems due to the negative impacts of globalization. This study uses a descriptive qualitative approach. The results of the research show that the guidance and counseling program is based on siri' cultural values ​​such as valuesGuilt-culture, (b) Shame-culture, (c) Fear-and-cultureeffective for alleviating youth problems due to the negative impact of globalization.